Field Testing of a Prestressed Concrete Bridge With High Performance and Locally Developed Ultra-High Performance Concrete Girders - Alahmari, Turki S.; Kennedy, Chris S.; Cuaron, Alain M.; Weldon, Brad D.; Jáuregui, David V. (Frontiers in Built Environment, 2019)
Recent research has developed mixture proportions for ultra-high performance concrete (UHPC) using materials primary local to New Mexico, United States of America (USA). In 2017, a two-span bridge was constructed in Anthony, New Mexico, USA consisting of prestressed girders using the locally developed non-proprietary UHPC, for span one, and high performance concrete (HPC), for the second span. Field tests were conducted on the bridge approximately nine months apart to investigate the performance and behavior of the UHPC and provide baseline data for future studies and condition evaluation of the bridge. The load tests consisted of various load configurations utilizing up to four trucks weighing 267 kN on average. The load paths were designed to maximize strains along the length of the bridge and investigate transverse load distributions between girders. The measured results provide a comparison of the behavior and performance of the UHPC and the HPC girders and were also compared to the American Association of State Highway and Transportation Officials (AASHTO) predicted behaviors. This study is one of the first that compares HPC and nonproprietary UHPC bridge performance subjected to the same environmental conditions and vehicular loading. The findings of the study will aid in the development of recommendations incorporating UHPC into design provisions as well as provide meaningful information of the short and long-term performance between the two materials including durability and load distribution.